2019
DOI: 10.18388/pb.2019_265
|View full text |Cite
|
Sign up to set email alerts
|

Aktywność biologiczna N6-furfuryloadenozyny

Abstract: Cytokininy stanowią jedną z grup hormonów roślinnych, które odgrywają ważną rolę we wzroście i rozwoju roślin. Wykazują różne efekty działania, szczególnie stymulują syntezę białek i uczestniczą w kontroli cyklu komórkowego. Pierwszą odkrytą cytokininą była N6-furfuryloadenina (kinetyna). Jest ona uważana za silny inhibitor procesów utleniania białek i kwasów nukleinowych w warunkach in vitro oraz in vivo. Zarówno kinetyna, jak i jej rybozyd (N6-furfuryloadenozyna, rybozyd kinetyny) jako naturalne związki wyst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…It has been reported that lycopene possesses more than twice the antioxidant capacity of beta-carotene, which is one of the strongest antioxidants in nature that delay aging [7] . Furthermore, lycopene can be incorporated into cosmetic formulations to develop products that effectively slow down skin aging [8] . With the continuous in-depth study of lycopene, scientific evidence has demonstrated the effective inhibition of esophageal cancer, prostate cancer, leukemia, etc., by lycopene [9] , [10] , [11] .…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that lycopene possesses more than twice the antioxidant capacity of beta-carotene, which is one of the strongest antioxidants in nature that delay aging [7] . Furthermore, lycopene can be incorporated into cosmetic formulations to develop products that effectively slow down skin aging [8] . With the continuous in-depth study of lycopene, scientific evidence has demonstrated the effective inhibition of esophageal cancer, prostate cancer, leukemia, etc., by lycopene [9] , [10] , [11] .…”
Section: Introductionmentioning
confidence: 99%